Key performance indicators of Olympic windsurfers during a World Cup: RS:X class® - Caraballo, I.; Domínguez, R.; Felipe, J. L.; Sánchez-Oliver, A. J. (Journal of Sports Sciences, 2022)
The aim of this study was to analyse differences in velocity, distance travelled and manoeuvres performed by Olympic sailors of the RS:X class using a GPS device. Fifty-three Olympic sailors of the RS:X class (28 males and 25 females) who competed in a World Championship were selected. The sample was divided into tertiles (T1, T2 and T3) according to their classification in the competition. Using a GPS device during the competition, mean velocity (VM), velocity made good (VMG), manoeuvres and distances in three different courses (upwind, reaching and downwind) were assessed during a regatta. Significant differences were found based on performance level in upwind (p < 0.001; 2p = 0.288), sailors of T1 covering a shorter distance compared to those of T2 (p < 0.009) and T3 (p < 0.001). Regarding VMG, an effect was observed for performance level in upwind (p < 0.001; 2p = 0.718), reaching (p < 0.001; 2p = 0.469) and downwind (p < 0.001; 2p = 0.575). Females covered a shorter distance compared to the males in upwind (p < 0.001; 2p = 0.639) and downwind (p < 0.001; 2p = 0.903). Distance and VMG are significant variables for establishing differences in performance level among Olympic sailors of the RS:X class when the wind speed is in a range of 8-21 knots.